Evaluation of sealing ability of Biodentine™ and mineral trioxide aggregate in primary molars using scanning electron microscope: A randomized controlled in vitro trial - Allwyn Samuel; Sharath Asokan; P R Geetha Priya; Seby Thomas (Wolters Kluwer Medknow Publications, 2016)
Objective: The aim of this study was to compare the sealing ability of mineral trioxide aggregate (MTA) and Biodentine™ when used to repair the furcal perforations in primary molars using scanning electron microscope (SEM). Study Design: The study sample comprised forty recently extracted primary molars. These teeth were placed in a 5.25% sodium hypochlorite solution for 24 h and washed with tap water. Access cavities were made using a round bur in high-speed handpiece. Perforations were made in the center of the floor of the pulpal chamber using a 0.5 mm round bur. The teeth were randomly assigned into two experimental groups based on the material used to seal the perforation: Group A - MTA and Group B - Biodentine™. The packed materials were allowed to set for 24 h. The samples were sectioned longitudinally and the extent of marginal adaptation was measured by SEM. Wilcoxon-signed rank test was used for statistical analysis using SPSS software. Results: All teeth exhibited microleakage, but Biodentine™ showed significantly less leakage (0.149) compared to MTA (0.583). Conclusion: Based on the results of this study, Biodentine™ showed lesser microleakage compared to MTA and thus may be a good alternative to MTA.